Exploring Managerial Barriers and Strategic Opportunities for E-Learning Deployment in Afghanistan - Hakimi, Musawer; Musawi, Sayed Zabihullah; Khaliqyar, Khudai Qul (Jurnal Ilmiah Manajemen & Bisnis, 2024)
E-learning has common meanings with the terms network-based education, distance learning, web-based education, and computer-based education. Today, e-learning is a common learning tool for education due to its effectiveness. Due to the Covid-19 lockdown, governments shifted their regular education to an e-learning system. Apart from opportunities, this shift created challenges and obstacles to its implementation. We aim to investigate the barriers and opportunities of e-learning deployment in public universities. Hence, a case study research was designed, and data was gathered through questionnaires and interviews with 96 individuals from Kunduz, Parwan, Kabul, Takhar, Ghor, and Samangan universities, encompassing diverse fields of study. The data were analysed using SPSS 26. According to this research, 63% of participants strongly agreed with the effectiveness of e-learning implementation. Furthermore, certain opportunities and obstacles emerged after the utilization of e-learning platforms by both students and lecturers. The challenges of e-learning deployment were lack of access to the internet, lack of stable electricity, and poverty. Contribution to the literature: In comparison with the existing literature, the current study provided an analysis of e-learning in its tension-filled relationship with the broader institutional structures and sociocultural realities of public universities in Afghanistan that circumscribe teaching and learning. The analysis provided entrées into infrastructural conditions, economic contexts, and socio-political circumstances that facilitate and inhibit the implementation of e-learning while offering suggestions for policymakers and practitioners in similar consideration of areas that are similarly unstable.